Improved Efficacy of Oral Immunotherapy Using Non-Digestible Oligosaccharides in a Murine Cow’s Milk Allergy Model: A Potential Role for Foxp3+ Regulatory T Cells - Vonk, Marlotte M.; Diks, Mara A. P.; Wagenaar, Laura; Smit, Joost J.; Pieters, Raymond H. H.; Garssen, Johan; van Esch, Betty C. A. M.; Knippels, Léon M. J. (Frontiers in Immunology, 2017)
Background: Oral immunotherapy (OIT) is a promising therapeutic approach to treat food allergic patients. However, there are some concerns regarding its safety and long-term efficacy. The use of non-digestible oligosaccharides might improve OIT efficacy since they are known to directly modulate intestinal epithelial- and immune cells in addition to acting as prebiotics. Aim: To investigate whether a diet supplemented with plant-derived fructo-oligosaccharides (FOS) supports the efficacy of OIT in a murine cow’s milk allergy model and to elucidate the potential mechanisms involved. Methods: After oral sensitization to the cow’s milk protein whey, female C3H/HeOuJ mice were fed either a control diet or a diet supplemented with FOS (1% w/w) and received OIT (10 mg whey) 5 days a week for 3 weeks by gavage. Intradermal (i.d.) and intragastric (i.g.) challenges were performed to measure acute allergic symptoms and mast cell degranulation. Blood and organs were collected to measure antibody levels and T cell and DC populations. Spleen-derived T cell fractions (whole spleen- and CD25-depleted) were transferred to naïve recipient mice to confirm the involvement of regulatory T cells (Treg) in allergy protection induced by OIT+FOS. Results: OIT+FOS decreased acute allergic symptoms and mast cell degranulation upon challenge and prevented the challenge-induced increase in whey-specific IgE as observed in sensitized mice. Early induction of Tregs in the mesenteric lymph nodes of OIT+FOS mice coincided with reduced T cell responsiveness in splenocyte cultures. CD25 depletion in OIT+FOS-derived splenocyte suspensions prior to transfer abolished protection against signs of anaphylaxis in recipients. OIT+FOS increased butyric acid levels in the caecum and serum galectin-9 levels. Conclusion: FOS supplementation improved the efficacy of OIT in cow’s milk allergic mice. Increased levels of Tregs, butyric acid and galectin-9 suggest a role for these mediators in the protective effect of OIT+FOS.